Haemophilus influenzae causes cellular trans-differentiation in human bronchial epithelia. Issue 3 (April 2021) - Glöckner, Michael; Marwitz, Sebastian; Rohmann, Kristina; Watz, Henrik; Nitschkowski, Dörte; Rupp, Jan; Dalhoff, Klaus; Goldmann, Torsten; Drömann, Daniel
Non-typeable Haemophilus influenzae (NTHi) is the most common respiratory pathogen in patients with chronic obstructive disease. Limited data is available investigating the impact of NTHi infections on cellular re-differentiation processes in the bronchial mucosa. The aim of this study was to assess the effects of stimulation with NTHi on the bronchial epithelium regarding cellular re-differentiation processes using primary bronchial epithelial cells harvested from infection-free patients undergoing bronchoscopy. The cells were then cultivated using an air-liquid interface and stimulated with NTHi and TGF-β. Markers of epithelial and mesenchymal cells were analyzed using immunofluorescence, Western blot and qRT-PCR. Stimulation with both NTHi and TGF-ß led to a marked increase in the expression of the mesenchymal marker vimentin, while E-cadherin as an epithelial marker maintained a stable expression throughout the experiments. Furthermore, expression of collagen 4 and the matrix-metallopeptidases 2 and 9 were increased after stimulation, while the expression of tissue inhibitors of metallopeptidases was not affected by pathogen stimulation. In this study we show a direct pathogen-induced trans-differentiation of primary bronchial epithelial cells resulting in a co-localization of epithelial and mesenchymal markers and an up-regulation of extracellular matrix components.